Efficient Screening of Long Oligonucleotides Against Hundred Thousands of SARS-CoV-2 Genome Sequences - Weidmann, Manfred; Graf, Elena; Lichterfeld, Daniel; Abd El Wahed, Ahmed; Bekaert, Michaël (Frontiers in Virology, 2022)
An unprecedented use of high-throughput sequencing for routine monitoring of SARS-CoV-2 viruses in patient samples has created a dataset of over 6 million SARS-CoV-2 genomes. To monitor genomes, deposited in the GISAID database, and to track the continuous sequence evolution of molecular assay oligonucleotide target sequences. A simple pipeline tool for non-experts was developed to mine this database for nucleotide changes in oligonucleotides and tested with the long oligonucleotides of a Recombinase polymerase amplification (RPA) assay targeting the RNA-dependent RNA polymerase (RdRP) gene of the SARS-CoV-2. Results indicate the emergence of a single nucleotide change in the reverse oligonucleotide from 0.03% to 26.23% (January to May 2021) in Alpha variant genomes, which however reduced to 17.64% by September after which the Alpha variant was completely displaced by the Delta variant. For all other variants, no relevant nucleotide changes were observed. The oligonucleotide screening pipeline allows efficient screening of nucleotide changes in oligonucleotides of all sizes in minutes.